ANALISIS 21st CENTURY-LEARNING DESIGN: KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA PADA MATA KULIAH TEORI PELUANG - Anandita Eka Febriana; Heni Pujiastuti (IKIP Siliwangi, 2022)
Communicative communication ability is one of the forms of ability that must be possessed by students to answer challenges in the 21st century, therefore research is needed to measure the level of mathematical communication skills in each student. This study aims to analyze and narrate the mathematical abilities of each student in probability theory lectures. This research was conducted using a qualitative approach with qualitative descriptive research. The research subjects were 6 students in the Mathematics Education study program at Sultan Ageng Tirtayasa University in the class of 2020. The way to collect data was by observation, instrument testing, and interviews. The indicators used are oriented to the rubric of skilled communication in 21st Century-learning design. The analysis technique used is an assessment using a scoring rubric and then categorizing the score results based on Arikunto's opinion. According to data research that has been done, it is found that students' mathematical communication skills are at the